SOME SUBSTANDARD METHODS OF THE SOLUTION OF EQUATIONS AND PROOF OF INEQUALITIES - Федак, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Twelve substandard methods of the solution of equations and proof of inequalities have considered.